Work-Life balance and perceived organizational support as predictors of quiet quitting among generation Z employees - Theresia Andhika Putri Pradani; Nita Rohayati; M. Choirul Ibad (Empathy : Jurnal Fakultas Psikologi, 2026)
This study examined the effects of work–life balance and perceived organizational support on quiet quitting among Generation Z employees in Karawang, Indonesia, from the perspective of person–organization fit theory. As Generation Z increasingly enters the workforce, organizations are experiencing shifts in workplace dynamics and employee expectations, particularly regarding work flexibility, meaningful work, and an inclusive organizational environment. Misalignment between employees' personal values and organizational culture may reduce motivation and emotional engagement, thereby increasing the likelihood of quiet quitting behaviors. A quantitative research design with a causal approach was employed. The participants consisted of 205 Generation Z employees (born between 1997 and 2007) working in Karawang, Indonesia. Data were collected using the Quiet Quitting Scale, the Work–Life Balance Scale, and the Survey of Perceived Organizational Support and were analyzed using multiple linear regression. The findings revealed that work–life balance and perceived organizational support jointly exerted a significant effect on quiet quitting, explaining 24% of the variance. Furthermore, both independent variables individually demonstrated significant negative associations with quiet quitting. These findings suggest that Generation Z employees who experience better work–life balance and stronger organizational support are less likely to engage in quiet quitting behaviors. The study contributes to the organizational behavior literature by extending the application of person–organization fit theory in explaining quiet quitting among Generation Z employees and offers practical implications for organizations seeking to enhance employee well-being and work engagement through supportive organizational practices.